Analisis anteseden loyalitas penggunaan web browser google chrome dengan job related it sebagai variabel moderating - KLEMENS WEDANAJI PRASASTYO (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to test and analyze empirically the influence of attitude toward computers, attitude toward search engine brand, satisfaction from engine brand, relationship with the search engine brand, and e-scape search engine on loyalty. The Job Related with IT used as moderating variable.The purposive sampling is used as sampling technique. This research was conducted on 200 respondents taken at office space at Sudirman street Jakarta. The research method used in this study was multiple regression. The result of this research shows that there is positive significant influence attitude toward computers, attitude toward search engine brand, satisfaction from engine of brand, relationship with the search engine brand, and e-scape search engine on loyalty. Job related IT was not found to have moderating effect on the relationship between all independent variables and loyalty.